Alternate Light Source Findings of Common Topical Cosmetics and Three Removal Methods. Issue 1 (15th October 2020) - Anderson, Jocelyn C.; Pollitt, Erin N.; Schildbach, Caroline; MacDonald, Ryan; Rose, Lauren; Sheridan, Daniel J.
ABSTRACT: Introduction: Alternate light sources (ALSs) are a tool used by forensic nurses to aid in the physical examination of patients. Prior research has shown some topical makeup products absorb alternate light similar to the absorption noted in bruises. Therefore, the purposes of this study were (a) to further examine the ALS findings of multiple brands and types of makeup products and (b) to compare the efficacy of three methods of makeup removal. Methods: Fourteen makeup products were applied to the forearms of 100 healthy adult volunteers with varying skin tones and then assessed under white light, six alternate light wavelengths, and three color filters, producing 19 total wavelength-and-filter combinations. The results were recorded before and after removal procedures by forensic nurse examiners who were blinded to the removal method. A three-arm randomized controlled trial of makeup removal methods (soap and water, isopropyl alcohol swab, makeup removal wipe) was conducted with the participants. Results: All 14 makeup products produced absorption in at least 10% of the observations. Fluorescence was observed in more than 10% of the observations for only two products. After product removal, four products continued to produce statistically significant absorption findings when viewed under an ALS. One product produced significant fluorescence after removal procedures. There were no statistically significant differences between the removal methods noted in any of these analyses. Conclusion: Our findings support the importance of using alternate light as one component of a comprehensive forensic examination, including history taking and physical examination.